Altered white matter microstructural connectivity in cluster headaches: A longitudinal diffusion tensor imaging study. (November 2014) - Chou, Kun-Hsien; Yang, Fu-Chi; Fuh, Jong-Ling; Huang, Chu-Chung; Lirng, Jiing-Feng; Lin, Yung-Yang; Lee, Pei-Lin; Kao, Hung-Wen; Lin, Ching-Po; Wang, Shuu-Jiun
Background: Functional and structural disruptions to the pain matrix, which may involve changes in white matter (WM) pathways connecting the pain-processing system and hypothalamus, have been implicated in the pathophysiology of cluster headache (CH). However, previous studies have obtained inconclusive results regarding WM changes in CH, and WM variations between "in-bout" and "out-of-bout" periods of CH remain to be determined. Methods: Multiple diffusivity indices obtained by diffusion tensor imaging (DTI) and post-hoc probabilistic tractography were used to elucidate CH pathophysiology. Results: Compared to healthy participants, in-bout CH patients showed regionally higher absolute (radial and mean) diffusivities in the left medial frontal gyrus and frontal sub-gyrus and lower absolute (axial, radial and mean) diffusivities in the right parahippocampal gyrus of the limbic lobe. These changes during the in-bout period generally persisted in the out-of-bout period, except for the left cerebellar tonsil. Post-hoc probabilistic tractography showed highly consistent anatomical connections between these altered areas and the hypothalamus across participants. Conclusions: Distinct WM changes were observed in episodic CH. Connections between the pain-modulation areas and hypothalamus may be involved in CH pathophysiology.